Umowa o współdziałanie na tle umów w administracji - Piechota-Oloś, Ewa (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2020)
The object of the analysis carried out in this paper is formed by the attempt to make a finding on the issue of the nature of the co-operative compliance agreement, reviewed from the point of view of agreements concluded within the framework of public administration. To that end, the author has reviewed the agreements concluded within the framework of administration that constitute one of the forms through which the public administration operates. In that regard, the extant views of the learned writing in administrative sciences on the place and the nature of agreements concluded within the remit of administrative law have been recalled here. Against the background of those views, the discrepancies regarding the features of the agreements within the framework of administration have been subjected to further study as regards the cooperative compliance agreement. Finally, making a finding on the nature of the new agreement introduced in the Polish tax law has led the author to declare a public-law nature of the co-operative compliance agreement.
Keywords: agreements within the framework of public administration; co-operative compliance agreement; co-operative compliance in thescope of tax law